Spectral and atmospheric characterization of 51 Eridani b using VLT/SPHERE - Samland, Matthias; Homeier, Derek (Astronomy and astrophysics, 2017)
Astronomy & Astrophysics (A&A) is an international journal which publishes papers on all aspects of astronomy and astrophysics